Dramatic Therapeutic Response to Dabrafenib Plus Trametinib in BRAF V600E Mutated Papillary Craniopharyngiomas: A Case Report and Literature Review - Fasano, Morena; Della Corte, Carminia Maria; Caterino, Marianna; Pirozzi, Mario; Rauso, Raffaele; Troiani, Teresa; Martini, Giulia; Napolitano, Stefania; Morgillo, Floriana; Ciardiello, Fortunato (Frontiers in Medicine, 2022)
Background Craniopharyngioma is a rare intracranial tumor, with a high morbidity rate due to its common refractiveness to conventional treatments. BRAF V600E mutation has recently been identified as the principal oncogenic molecular driver of papillary craniopharyngiomas (PCP), one of the two main variants of craniopharyngioma. Case Presentation A 49-year-old man with recurrent craniopharyngioma, harboring BRAF V600E mutation, has been treated with targeted therapy based on a combination of a BRAF-inhibitor, dabrafenib (150 mg, orally two times daily), and a MEK-inhibitor, trametinib (2 mg, orally two times daily). Before starting treatment, the patient was symptomatic: he lamented confusion, dysphasia, and intense fatigue, that did not allow him to work normally. After just one cycle of treatment, the patient showed an important clinical improvement, reporting a progressive regression of the basal symptoms, hinting at a rapid and dramatic response, which was confirmed at the first radiological assessment. Thus, treatment was continued and at the time of writing, the treatment is still ongoing (total duration of treatment: 14 months) and it is well tolerated, with very good quality of life: the patient has no limitations in daily activities and he has even been able to restart to work. Conclusion The use of targeted therapies—as a clinical practice or in clinical trials—represents an important therapeutic alternative and a great evolution for patients' prognosis vs. the standard of care, historically represented by unselected chemotherapies. The discovery of the BRAF V600E mutation in patients with PCP is very rare, resulting in a lack of data on the efficacy of the combination of dabrafenib and trametinib.